The effect of mandatory paid sick leave laws on labor market outcomes, health care utilization, and health behaviors - Kevin Callison; Michael F. Pesko (W.E. Upjohn Institute for Employment Research, 2016)
We evaluate the impact of paid sick leave (PSL) mandates on labor market outcomes, the utilization of health care services, and health behaviors for private sector workers in the United States. By exploiting geographic and temporal variation in PSL mandate adoption, we compare changes in outcomes for workers in counties affected by a PSL mandate to changes for those in counties with no mandate. Additionally, we rely on within-county variation in the propensity to gain PSL following a mandate to estimate policy effects for workers most likely to acquire coverage. Results indicate that PSL mandates lead to increased access to PSL benefits, especially for women without a college degree. We find that PSL laws reduce average weekly hours worked and private sector employment, but appear to have no effect on job tenure or labor force participation. PSL mandates are associated with sizable reductions in emergency department utilization and increases in general practitioner visits. Finally, we present suggestive evidence that PSL mandates lead to more days binge drinking.
Keywords: I18; I12; J21; J23; J32; 330; Paid sick leave; labor market; health care; health behaviors